Genetic variations of Bornean frog, limnonectes leporinus as inferred by mitochondrial DNA of cythocrome c oxidase I (COI) - Ibrahim, bin Bujang. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Genetic variation was examined between two different sample locations : Limnonectes leporinus from Bau and Limnonectes leporinus from Matang. Overall 10 sample were isolated; 6 samples from Bau and 4 samples from Matang. Genetic variation was examined using PCR and DNA sequencing analysis of cythrome oxidase I (COl) mtDNA gene. By DNA sequence analysis 10 individuals were successfully sequenced with the size of 459 -479 bp. The range of sequence divergence among haplotypes showed high levels of variation within (0.2% -9.0%) and among (2.0% -9.4%) population of Limnonectes leporinus. An addition, phylogenetic analysis showed the existence of genetic variation between Bau and Matang population. Maximum Parsimony analysis yielded the best construction of phylogenetic tree. Two main clusters were apparent in the ingroup, including the samples from Bau population and sample from Matang population. This indicates that COl yielded the ultimate level of resolution of genetic variation and a good marker for diagnosis of genetic variation. Further analysis with higher amount of samples from other populations are needed to strengthen the result of this study.